Florística e fenologia reprodutiva da flora vascular e plasticidade fenotípica de Miconia chamissois Naudin em mata de galeria com transição para campo sujo úmido - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The gallery forests are forest communities that form galleries on the watercourse of streams and small rivers. Wetlands, on the other hand, are herbaceous-shallow formations occurring on land that is periodically or permanently soaked, in areas with upwelling, or in closed depressions, which accumulate water during the rainy season. The wetlands are found in narrow transition strips between the cerrado (lato sensu) and the gallery forests, along permanent or temporary water courses, occupying wide plains or associated with areas of springs. The work of floristic surveys, phenology and phenotypic plasticity in these areas are incipient and those that exist are concentrated in the region of the Federal District. In this context, the objective of the present study was to survey the species and reproductive phenology of the vascular flora and to evaluate the variation in the leaf traits of Miconia chamissois Naudin in a gallery forest with a transition to wetland in Quirinópolis, GO. The study area is located in the headland of Córrego Formiga and is part of the urban perimeter. The dissertation is composed of two chapters: Chapter I - Floristics and reproductive phenology of the vascular flora of gallery forest with transition to wetland, and Chapter II - Phenotypic plasticity of Miconia chamissois Naudin (Melastomataceae) in gallery forest and dirty field humid For the accomplishment of floristics and phenology 20 trails distributed perpendicular to the watercourse were demarcated. Data collection took place from April 2017 to January 2019. A total of 219 species were recorded, distributed in 170 genera and 69 families. The similarity indices of the present study with the others were low or nonexistent. A total of 18 new species records were sampled for the state of Goiás. About 58% of the species had flowering and fruiting throughout the period evaluated. These results corroborate the existence of a high floristic diversity, which provides important resources for the fauna. For the analysis of phenotypic plasticity the species Miconia chamissois Naudin was selected because of the abundance in the gallery forest and in the humid dirty field. Data collection was performed in November and December 2018 and January 2019. Ten leaves of each individual were collected, 30 individuals in the gallery forest and 30 in the dirty field, resulting in 600 leaves. Then, the width and length of the limbus and the length of the petiole were measured. The shrub architecture of Miconia chamissois (total height and length, width and crown area) was measured and the environmental variables were collected for all individuals at the edge of the gallery forest and in the wet dirty field. For the environmental variables the data of humidity, soil temperature and terrain slope were measured. The correlation test and the NMDS were used in the R program to test the axes that best explain the response variables as a function of the explanatory variables. The shrub architecture of the individuals of Miconia chamissois was higher in the gallery forest than in the dirty field. The environmental variables and the foliar measurements were also higher for the gallery forest. The results for the leaf traits overlap in the gallery forest and in the humid dirty field, however, it is observed that the larger the declivity the lower the values of leaf structure and the higher the value of the soil temperature the greater the leaf metrics. Thus, we conclude that the environmental variables exert influence on the morphological characteristics of the species, being able to influence both the leaf structures and the architecture of the species.
Keywords: Cerrado; Áreas úmidas; Diversidade; Frutificação; Cerrado; Wetlands; Diversity; Fruiting; CIENCIAS BIOLOGICAS